Screening and cellular validation of prognostic genes regulated by super enhancers in oral squamous cell carcinoma. Issue 2 (20th December 2021) - Zhang, Liru; Li, Huanju; Qiu, Yongle; Liu, Yuanhang; Liu, Xin; Wang, Wenjing
ABSTRACT: Oral squamous cell carcinoma (OSCC) is the leading cause of death in patients with head and neck cancer. Reliable biomarkers to guide treatment decisions for OSCC remain scarce. The purpose of this study was to identify novel prognostic markers regulated by super enhancers in OSCC. Eight modules were obtained by weighted gene co-expression network analysis (WGCNA), among which MEblue module had the highest correlation with tumor stage, alcohol consumption and smoking. There were 41 genes regulated by super enhancers in MEblue module. Functional analysis showed that 41 super enhancer-regulated genes were involved in cancer progression. A total of twenty transcription factors of the 41 genes were predicted. Prognostic analysis of the 41 genes and the top 5 transcription factors showed that patients with high expression of AHCY, KCMF1, MANBAL and TFDP1 had a poor prognosis. Immunohistochemical analysis showed that AHCY, KCMF1 and MANBAL were highly expressed in OSCC tissue. Cellular experiment demonstrated that TFDP1 promoted AHCY, KCMF1 and MANBAL expression by binding to the super enhancers of these genes. Knockdown of TFDP1, AHCY, KCMF1 and MANBAL inhibited the proliferation of OSCC cells. In conclusion, AHCY, KCMF1 and MANBAL were recognized as super enhancer-regulated prognostic biomarkers regulated by TFDP1 in OSCC.